Pre-transfusion testing for Ebola virus disease patients in serious communicable infectious diseases hospitals in Tokyo: A cross-sectional study. Issue 7 (July 2019) - Sakamoto, Naoya; Kosaka, Atsushi; Imamura, Akifumi; Uchiyama-Nakamura, Fukumi; Iwabuchi, Sentaro; Nishimura, Shigeko; Fujita, Hiroshi
Abstract: Background: Ebola virus disease (EVD) was endemic to Africa in 2014–2016. Supportive therapies have been shown to improve the outcome of EVD, and additional supportive therapy including blood transfusion therapy and external circulation could be needed in the event of a future global outbreak. However, pre-transfusion testing policies and guidelines have not yet been established in Japan. Methods: We conducted a cross-sectional study of blood transfusion therapy for EVD patients at three designated hospitals for serious communicable diseases in Tokyo. In each hospital, we surveyed blood transfusion therapy policy, blood transfusion protocol, presence of a specialist in the department of transfusion medicine, facility capacity for pre-transfusion compatibility testing, and types of personal protective equipment available. Results: One hospital had a cross-matched compatible blood transfusion policy, one had a cross-matched compatible blood transfusion policy only when the patient's ABO and RhD type is previously known, and the third had not created a policy. Two hospitals had a department of transfusion medicine. These two hospitals had a special testing unit for serious communicable diseases, while the other had a portable unit for testing. There were no major differences noted in available personal protective equipment. Conclusion: Policies and protocols differ among hospitals. The choice of blood transfusion policy and pre-transfusion testing is largely dependent on equipment and human resources. Further discussion is required to develop national guidelines for blood transfusion therapy in patients with serious communicable diseases, including countermeasures against complications and ethical issues related to the safety of patients and healthcare workers.